Domain Swapping and Gene Shuffling Identify Sequences Required for Induction of an Avr-Dependent Hypersensitive Response by the Tomato Cf-4 and Cf-9 Proteins - Wulff, Brande B. H. (American Society of Plant Physiologists, 2001)
The tomato Cf-4 and Cf-9 genes confer resistance to infection by the biotrophic leaf mold pathogen Cladosporium. Their protein products induce a hypersensitive response (HR) upon recognition of the fungus-encoded Avr4 and Avr9 peptides. Cf-4 and Cf-9 share >91% sequence identity and are distinguished by sequences in their N-terminal domains A and B, their N-terminal leucine-rich repeats (LRRs) in domain C1, and their LRR copy number (25 and 27 LRRs, respectively). Analysis of Cf-4/Cf-9 chimeras, using several different bioassays, has identified sequences in Cf-4 and Cf-9 that are required for the Avr-dependent HR in tobacco and tomato. A 10–amino acid deletion within Cf-4 domain B relative to Cf-9 was required for full Avr4-dependent induction of an HR in most chimeras analyzed. Additional sequences required for Cf-4 function are located in LRRs 11 and 12, a region that contains only eight of the 67 amino acids that distinguish it from Cf-9. One chimera, with 25 LRRs that retained LRR 11 of Cf-4, induced an attenuated Avr4-dependent HR. The substitution of Cf-9 N-terminal LRRs 1 to 9 with the corresponding sequences from Cf-4 resulted in attenuation of the Avr9-induced HR, as did substitution of amino acid A433 in LRR 15. The amino acids L457 and K511 in Cf-9 LRRs 16 and 18 are essential for induction of the Avr9-dependent HR. Therefore, important sequence determinants of Cf-9 function are located in LRRs 10 to 18. This region contains 15 of the 67 amino acids that distinguish it from Cf-4, in addition to two extra LRRs. Our results demonstrate that sequence variation within the central LRRs of domain C1 and variation in LRR copy number in Cf-4 and Cf-9 play a major role in determining recognition specificity in these proteins.